The Effect of NaCl 0.9% and Chlorhexidine for Oral Care on the Ph of Unconscious Intubated Patients’ Mouths - Rantung, Gilny; Silton, Daniel; Rantung, Jeanny (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
The mouth of an unconscious intubated patient tends to open, causing a dry mouth. Then the pH in the mouth becomes more acidic, increasing the tendency for bacteria to colonize. The aim of the study was to assess the effect of NaCl 0.9% solution and Chlorhexidine 0.2% solution on the pH of unconscious intubated patients' mouths in an intensive care unit. Using an experimental-research design, 20 patients were selected purposively and were divided into two groups. The Group 1 patients were given oral hygiene by the use of a NaCl 0.9% solution (control group). The Group 2 patients were given oral hygiene by the use of a Chlorhexidine 0.2% solution. The procedure was repeated within 4 hours of the first procedure. Before and after the procedures, the pH of the patients' mouths was assessed with pH paper. The oral-hygiene mean score of Group 1 after the 1st and 2nd treatments was 0.22 and 0.23, respectively. In Group 2, the pH after the 1st and 2nd treatments was 0.35 and 0.3, respectively. The data showed no significant differences in pH mean scores between Group 1 and Group 2. NaCl 0.9% and Chlorhexidine 0.2% were indicated to be ineffective for increasing the pH level of unconscious-intubated patients. However, NaCl 0.9% tended to increase pH levels, although they were still within an acidic level. Keywords : NaCl, Chlorhexidine, oral care, unconscious-intubated patients